Răspuns :
Explicație pas cu pas:
[tex] \large \bf \dfrac{61}{35 } - \dfrac{2x}{35} = \dfrac{19}{35} + \dfrac{22}{35} [/tex]
[tex] \large \bf \dfrac{61 - 2x}{35} = \dfrac{19 + 22}{35} [/tex]
[tex] \large \bf 35 \cdot(61 - 2x) =35 \cdot 41 \: \: | : 35[/tex]
[tex]\large \bf 61 - 2x =41 [/tex]
[tex]\large \bf 61 =41 + 2x[/tex]
[tex]\large \bf 61-41 = 2x [/tex]
[tex]\large \bf x = 20 : 2[/tex]
[tex]\Large \boxed{ \bf x = 10}[/tex]
==pav38==
Răspuns:
61/35-2x/35=19/35+22/35
2x/35=61/35-41/35
2x/35=20/35
2x=20
x=20:2=>x=10